The Implementation of Education for Sustainable Development (ESD)-Based Natural Science Learning to Empower Critical Thinking Skills and Scientific Literacy - Bramastia; Suciati; Budi Utami; Kadek Dwi Hendratama Gunawan; Endah Febri Setiya Rini (Postgraduate, University of Mataram, 2025)
Education for Sustainable Development (ESD)-Based Science learning is important for strengthening students’ scientific literacy and critical thinking skills. This study aims to analyze ESD-based science learning conducted by teachers affiliated with the Surakarta City’s Subject Teacher Forum (MGMP) for Natural Science. This research uses a qualitative descriptive approach. The sample used in this research consisted of 25 teachers affiliated with the Surakarta City’s MGMP for Natural Science. Data collection was carried out through observation, interviews, questionnaires and documentation. The data analysis technique used is Miles and Huberman’s interactive analysis method. The results of research show that the majority of teachers understand the concept of ESD, are able to design contextual learning, and facilitate reflective activities and projects relevant to sustainability issues. Learning encourages the students to think critically, discuss, and develop scientific literacy in an applied manner. However, challenges are still encountered in teaching material preparation and limited learning resources. This study emphasizes the urgency of training, policy support, and institutional synergy to strengthen the sustainability of ESD implementation in Natural Science education.